2018
DOI: 10.1177/2398212818776475
|View full text |Cite
|
Sign up to set email alerts
|

Progress in Neuroengineering for brain repair: New challenges and open issues

Abstract: In recent years, biomedical devices have proven to be able to target also different neurological disorders. Given the rapid ageing of the population and the increase of invalidating diseases affecting the central nervous system, there is a growing demand for biomedical devices of immediate clinical use. However, to reach useful therapeutic results, these tools need a multidisciplinary approach and a continuous dialogue between neuroscience and engineering, a field that is named neuroengineering. This is becaus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 119 publications
(138 reference statements)
0
30
0
Order By: Relevance
“…Neurodegenerative and neurological diseases like Alzheimer’s disease and Parkinson’s disease threaten an ever-increasing percentage of our ageing population. Studies have shown that deep brain stimulation and recovery of sensory capabilities by electrical stimulation based on neural recordings are extremely beneficial to neural regeneration [ 66 ]. Hence studying neural signals in the brain is critical for understanding the intrinsic neural pathways in neural regeneration.…”
Section: Applications Of Graphene-based Nanomaterials In Neural Timentioning
confidence: 99%
“…Neurodegenerative and neurological diseases like Alzheimer’s disease and Parkinson’s disease threaten an ever-increasing percentage of our ageing population. Studies have shown that deep brain stimulation and recovery of sensory capabilities by electrical stimulation based on neural recordings are extremely beneficial to neural regeneration [ 66 ]. Hence studying neural signals in the brain is critical for understanding the intrinsic neural pathways in neural regeneration.…”
Section: Applications Of Graphene-based Nanomaterials In Neural Timentioning
confidence: 99%
“…As proposed by Arksey and O'Malley [87], we utilized the recommended five step process of scoping studies: identifying the review's research purpose and question, identifying databases to search, recording the descriptive quantitative results, selecting literature based on descriptive quantitative results for qualitative analysis, qualitative analysis of data, and reporting findings of qualitative analysis. We did not perform the optional step [6] of consulting stakeholders to execute knowledge translation for this study because that is part of a follow up study.…”
Section: Academic and Newspapersmentioning
confidence: 99%
“…Neuroscientific and neurotechnological advancements (from now on called neuro-advancements) have a long history and continue to develop and grow [1][2][3][4][5][6][7]. Neuroscience is " .…”
Section: Introductionmentioning
confidence: 99%
“…One of the challenges is that key state of the art methods, such as deep learning, that have had huge successes in other applications may not be the best approach for the constraints imposed by the needs of BMI ( Vidaurre et al, 2015 ). In a recent paper, Panuccio et al (2018) do an excellent job summarizing the current state and challenges of neural engineering aimed at restoring neural function, including proposing a number of similar requirements discussed in the current paper, that emerging algorithms and machine learning will need to address in order to build a true adaptive BMI.…”
Section: Integration Of Bmi With Machine Learningmentioning
confidence: 99%